Modelling and simulation of passive bistatic radar - Xia, Yu (2017)
Passive bistatic radar (PBR) systems have separate transmitter and receiver. It usually uses a third-party transmitter to track targets. Transmitter and receiver are widely spaced. Passive radar has a lot of advantages compared to monostatic radar. It is used in many areas because of enhanced surveillance. However, the complexity of PBR systems is high, there are a lot of challenges to design a PBR system experimentally. This project develops modelling and simulation of PBR. It studies on developing radar algorithms, target detection and how to reduce environment effects. For this project, effect of multipath in passive radar system is taken into consideration.